Pengaruh Media Dalam Bias Anti-China Di Masa Pandemi Covid-19 Di Amerika Serikat - Paula Rita Wijayanti; Suzie Sri Suparin S. Sudarman (Jayapangus Press, 2023)
This study discusses immigrants from China and Chinese-Americans who are the largest immigrant groups from Asia. Based on history, economic conflicts motivated by sentiments have been experienced by Chinese immigrants in which the American government issued the Chinese Exclusion Act 1882 which prohibited Chinese immigrants from entering America for 10 years. Stereotypes such as “yellow-peril” and “minority model” which are influenced by technological and media developments have also emerged as a form of discrimination against Chinese immigrants. This study discusses the anti-China sentiment that stirred again during the Covid-19 pandemic. At the end of 2019, the Covid-19 virus that originated in Wuhan, China began to spread throughout the world, one of which was to the United States. The President at the time, Donald Trump tweeted through his Twitter account which contain anti-China sentiments, and this had an impact on anti-China turmoil in America, including the impact on immigrants from China and Chinese-Americans. This study uses qualitative methods with literature analysis techniques in analyzing the research corpus. This study attempts to describe the history of anti-China sentiment that has developed in the United States and highlights the role of the media in anti-China racism. This research also concludes that anti-China sentiment persists, even during this Covid-19 pandemic. This study also found that indirectly the media old or new media, played a major role in helping perpetuate racism in the United States.